2019
DOI: 10.1038/s41467-019-12262-x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nicotinamide riboside metabolism protects against diet-induced liver damage

Abstract: Supplementation with the NAD+ precursor nicotinamide riboside (NR) ameliorates and prevents a broad array of metabolic and aging disorders in mice. However, little is known about the physiological role of endogenous NR metabolism. We have previously shown that NR kinase 1 (NRK1) is rate-limiting and essential for NR-induced NAD+ synthesis in hepatic cells. To understand the relevance of hepatic NR metabolism, we generated whole body and liver-specific NRK1 knockout mice. Here, we show that NRK1 deficiency lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 43 publications
9
46
0
Order By: Relevance
“…NAFLD mice, hepatocytes with endoplasmic reticulum stress) [55][56][57][58] . However, other studies have found no direct effect of NAM supplementation on NAD+ levels 18,59 . If the extra NAD that is synthesized, is readily used for deacetylation, then you would not see a significant increase.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…NAFLD mice, hepatocytes with endoplasmic reticulum stress) [55][56][57][58] . However, other studies have found no direct effect of NAM supplementation on NAD+ levels 18,59 . If the extra NAD that is synthesized, is readily used for deacetylation, then you would not see a significant increase.…”
Section: Discussionmentioning
confidence: 94%
“…After 7 days, malnourished subgroups were treated with modulators of the TRP-NAM pathway until sacrifice on day 14. Nicotinamide, nicotinamide-riboside and tryptophan were given by drinking water in a dose of 160 mg/kg body weight/day, and methionine was included in diets at a concentration of 0.75 g/kg diet 15,59,63 . Nicotinamide, nicotinamide-riboside and tryptophan were provided by Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Animals and Diets A Breeding Colony Of C57bl/6 Mice Was Obtmentioning
confidence: 99%
“…This also constitutes the first observation of substantive NR concentration in non-supplemented human tissues. The role of endogenous NR metabolism has been heightened by recent observation that loss of hepatic NRK1 expression depresses liver function and that endogenous hepatic NRK1 expression declines in mice on high fat diet (29,35).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in rodent models, supplementation of either NA (43,44) or NR(26) can protect against alcoholic liver injury. On the basis of recent data showing that NR has the highest level of hepatic oral availability of the NAD + precursor vitamins (25), that endogenous NR metabolism protects the liver (29,35) and that high dose NR is safe and potentially valuable in and fatty liver (45), measures to increase NAD + content in human liver might be of clinical benefit. Vitamin B1 supplementation is well established in ArLD, primarily for the prophylaxis or treatment of Wernicke's encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation